More pain, more tender points: is fibromyalgia just one end of a continuous spectrum?. Issue 7 (July 1996) - Croft, P; Burt, J; Schollum, J; Thomas, E; Macfarlane, G; Silman, A
Abstract : OBJECTIVES: To investigate the hypothesis that fibromyalgia represents one end of a spectrum in which there is a more general association between musculoskeletal pain and tender points. METHODS: The subjects studied were 177 individuals selected from a population based screening survey for musculoskeletal pain. All subjects completed a pain mannikin and were examined for the presence of tender points at the nine American College of Rheumatology bilateral sites. RESULTS: There were moderately strong associations (odds ratios range 1.3-3.1) between the reported presence of pain in a body segment and the presence of a tender point within that segment. Further, there was evidence of a trend of increasing number of tender points with increasing number of painful segments. The reporting of non-specific pain, aching, or stiffness, was also associated with high tender point counts. CONCLUSION: This study illustrates that the association between tender points and pain is not restricted to the clinically defined subgroup with chronic widespread pain. Given that widespread pain and tender points have previously been linked with distress, this might reflect lesser degrees, or earlier phases of the somatisation of distress.